Behaviour and cardiac response to stress in signal crayfish exposed to environmental concentrations of tramadol - Ložek, F; Kuklina, I; Grabicová, K; Kubec, J; Buřič, M; Grabic, R; Randák, T; Císař, P; Kozák, P (Aquatic toxicology (Amsterdam, Netherlands), 2019)
Evidence of the ecological and biological impact of pharmaceuticals in surface waters on aquatic organisms is increasing. Tramadol is a synthetic opioid analgesic used to treat chronic and acute pain. To investigate its long-term effects at environmentally relevant levels, we evaluated heart rate (HR) and locomotion of signal crayfish Pacifastacus leniusculus during a 21-day exposure to 1 μg L-1 tramadol followed by 14 days depuration. Locomotion and HR were recorded over a period 30 min before and 30 min after exposure to physiological fluids of an injured conspecific, a natural stressor, four times during the tramadol exposure and four times during depuration. A significant increase in HR following stress induction was found in the majority of tramadol-exposed and control crayfish, as well as significant group-specific HR changes between both groups. Locomotor activity during tramadol treatment differed from that during depuration, in general showing less time spent in locomotion and lower distance moved. The tramadol exposed crayfish exhibited higher velocity during depuration than during the exposure period. Results may suggest a potential shift in prey-predator relationships.
Keywords: chemické látky znečišťující vodu; Invertebrate; Behavior, Animal; srdce; Heart Rate; Aquatic organism; Water Pollutants, Chemical; tramadol; srdeční frekvence; Cardiac physiology; lokomoce; Stress, Physiological; Time Factors; Animals; Locomotion; Tramadol; Ethology; zvířata; Pharmaceutical pollution; časové faktory; Environmental Exposure; severní raci; chování zvířat; Analgesic; Crayfish; Predation risk; Heart; fyziologický stres; vystavení vlivu životního prostředí; Astacoidea